2020
DOI: 10.3390/jmse8050306
|View full text |Cite
|
Sign up to set email alerts
|

Damage in Rubble Mound Breakwaters. Part II: Review of the Definition, Parameterization, and Measurement of Damage

Abstract: Damage in rubble mound breakwaters has been addressed for more than 80 years and, as reported in “Part I: Historical review of damage models”, a considerable number of hydraulic instability models have been proposed up to date. Most of them were developed from small-scale physical tests, based on damage descriptors not always parameterized nor measured in the same way, which indeed complicates the comparison and reproducibility from different experimental data sources. The latter is increased by the lack of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Campos et al 197 reviewed the definition, parameterization, and measurement of damage in rubble mound breakwaters. They suggested that damage is characterized following a visual approach or a measuring approach, which is based on a 2D or 3D profile reconstruction.…”
Section: Port Structuresmentioning
confidence: 99%
“…Campos et al 197 reviewed the definition, parameterization, and measurement of damage in rubble mound breakwaters. They suggested that damage is characterized following a visual approach or a measuring approach, which is based on a 2D or 3D profile reconstruction.…”
Section: Port Structuresmentioning
confidence: 99%
“…Techniques for assessing and measuring lab-scale physical models, with a focus on examining the behavior of RMBs under wave action, have advanced significantly in recent years. Laboratory investigations exploring this subject employ a range of scanning devices, including structured light scanners, infrared scanners, and laser scanners, along with conventional profilers [6]. Some studies have also integrated devices with additional depth measurement capabilities, such as time-of-flight (ToF) and RGB-D cameras (e.g., Kinect) [7][8][9][10], providing the advantage of collecting information from the submerged portions of RMB models.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as will be described later, numerical calculations are useful, and various numerical models without fixed grids have also been developed to examine the functions of block mound breakwaters: the Lagrangian models were applied by [8][9][10], whereas a mesh adaptation method was used by [11] to reproduce the detailed flow around a deformed block. The damage in rubble mound breakwaters has been summarized based on historical and future perspectives by [12,13].…”
Section: Introductionmentioning
confidence: 99%